Предмет: Алгебра,
автор: foundy
У в квадрате -(9у-2):7=0
Ответы
Автор ответа:
0
Решение:
Приведём уравнение к общему знаменателю:
7y^2-9y+2=0
y1,2=(9/2+-D)/2*7 D=sqrt(81/4-4*7*2)=sqrt(81/4-224/4)=sqrt(-143/4)
y=9/2/14=9/28
Приведём уравнение к общему знаменателю:
7y^2-9y+2=0
y1,2=(9/2+-D)/2*7 D=sqrt(81/4-4*7*2)=sqrt(81/4-224/4)=sqrt(-143/4)
y=9/2/14=9/28
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: ajnurtausogarova
Предмет: Английский язык,
автор: sofya2794
Предмет: Математика,
автор: romka1102
Предмет: Физика,
автор: Марья7